Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Minimal modification to displacement ventilation for significant improvement through air redistribution - Zi Cheng; Jingkai Wang; Zhenying Zhang; Hao Simone Wang; Yibin Lu; Zekai Mu; Jian Liu; Zhang Lin (Building and Environment, 2026)

Life-course body shape trajectories and cerebral oxygen metabolism in community-dwelling older adults - Yifan Yan; Yaping Zhang; Xuhao Zhao; Renwei Chen; Shenghao Fang; Yi Zhou; Jingkai Huang; Fuyan Wang; Christopher Chen; Zixuan Lin; Xin Xu (GeroScience, 2026)
Obesity and lifelong body-shape fluctuation are associated with late-life structural brain damage, suggesting the involvement of metabolic pathways. The cerebral metabolic rate of oxygen (CMRO₂) reflects hemodynamic and oxidative stress and precedes structural atrophy, but its role in adiposity-related brain change remains unclear. We examined whether current and life-course adiposity relate to CMRO₂ and to structural change. A total of 303 community-dwelling adults aged 50 years and older were included. Body shape was assessed using Body Mass Index (BMI) and Body Roundness Index (BRI). Global CMRO₂ was derived from TRUST and phase-contrast MRI. T1-weighted MPRAGE provided volumetry, and medial temporal atrophy (MTA) grading. General linear models estimated associations of BMI and BRI with CMRO₂, including age interactions. Age-stratified mediation tested CMRO₂ as a mediator of adiposity to MTA associations. Body-shape trajectories at ages 25, 40, 60, and current age were modeled and related to CMRO₂ and metabolism-related regions. Adiposity was associated with lower CMRO₂: with overweight (β = -1.12 μmol/100 g/min, 95%CI = (-1.96, -0.28)) and higher BRI (β = -1.31, 95%CI = (-2.36, -0.27)) showing stronger effects with advancing age. Among participants aged 70 years, CMRO₂ mediated the association between BMI and MTA (indirect β = 0.06, 95%CI = (0.01, 0.14)). Three adulthood body-shape patterns emerged, and CMRO₂ was lower in moderate increasing (β = -11.40; 95%CI = (-20.90, -1.90)) and high-rising (β = − 12.23; 95%CI = (-23.56, -0.90)) groups. Metabolism-related regions were larger in higher-risk patterns, particularly the left hypothalamus. Greater and prolonged adiposity is linked to reduced CMRO₂ and related structural differences in older adults.

Enhancing thermal comfort in shared building spaces: A group thermal preference framework and optimization strategies - Jingkai Wang; Zi Cheng; Yibin Lu; Zhang Lin (Building and Environment, 2026)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Spirulina-derived atomically dispersed Fe–N4 sites on g-C3N4 for efficient CO2 photoreduction - Haoxian Wang; Junjie Wang; Jin Xu; Jingkai Lin; Zhongshuai Zhu; Yazi Liu; Feihu Mu; Bin Huang; Fei Yu; Chenmin Xu; Shaogui Yang; Huan He; et al. (Chemical Engineering Journal, 2025)

A 3D interwoven Pt@CNTs network embedded in ZnIn2S4 microspheres for Schottky-driven photothermal hydrogen evolution - Junjie Hao; Ning Li; Jingkai Lin; Chaorui Xue; Qing Chang; Xiangqian Fan; Huinian Zhang; Caihong Hao; Huayang Zhang; Shengliang Hu (Chemical Engineering Journal, 2025)

Engineering a complete mevalonate pathway in Chlamydomonas reinhardtii for enhanced isoprenoid production - Jingkai Wang; Muhammad Anwar; Jiancheng Li; Lin Dan; Bin Jia; Zhangli Hu (Algal Research, 2025)

Novel high-performance endothermic fuels from quasi-homogeneous nano-engineering - Ji Mi; Peilun Wang; Hongshang Wang; Chongkun Shao; Zhiyuan Yuan; Jingkai Ma; Yongsheng Guo; Xufeng Lin; Wenjun Fang (Fuel, 2025)

TROPOMI unravels transboundary transport pathways of atmospheric carbon monoxide in Tibetan Plateau - Peize Lin; Yuan Tian; Tobias Borsdorff; Zhiwei Li; Jochen Landgraf; Hongyu Wu; Jingkai Xue; Dake Ding; Hang Ye; Yizhi Zhu; Cheng Liu (Science of The Total Environment, 2024)

Utilizing spontaneous plants for sustainable development in residential green spaces: Insights from environmental drivers and niche analysis in Fuzhou City, China - Chengyu Ran; Junyi Pan; Yuxin Lin; Tongyan Li; Yaling Huang; Jingkai Huang; Shiyuan Fan; Wenqiang Fang; Shuang Zhao; Yuxiang Liu; Jiali Jin; Weicong Fu (Journal of Environmental Management, 2024)

Studies on regional ozone formation sensitivities and transport with higher spatiotemporal resolutions in a stereoscopic dimension: GEMS and vertical observations - Haochen Peng; Chengzhi Xing; Yikai Li; Chengxin Zhang; Jinan Lin; Jingkai Xue; Xiaohan Wang; Yuhang Song; Xinhan Niu; Cheng Liu (Atmospheric Research, 2024)

The microclimate impact of treetop walk based on plant community simulation - Ying Lin; Shanjun Huang; Han Xu; Wenqiang Fang; Chenfei Gao; Jingkai Huang; Weicong Fu (Environmental Science and Pollution Research, 2024)

Insight into copper-cerium catalysts with different Cu valence states for CO-SCR and in-situ DRIFTS study on reaction mechanism - Jinfeng Li; Jiexuan Zhu; Shiying Fu; Lin Tao; Bingxian Chu; Qiuju Qin; Jingkai Wang; Bin Li; Lihui Dong (Fuel, 2023)

m6A writer WTAP targets NRF2 to accelerate bladder cancer malignancy via m6A-dependent ferroptosis regulation - Ke Wang; Gang Wang; Gang Li; Wei Zhang; Yarong Wang; Xiaofeng Lin; Chengxian Han; Hanxuan Chen; Liang Shi; Abudoula Reheman; Jingkai Li; Zhaomin Li; et al. (Apoptosis, 2023)

Leveraging single-cell Raman spectroscopy and single-cell sorting for the detection and identification of yeast infections - Jingkai Wang; Siyu Meng; Kaicheng Lin; Xiaofei Yi; Yixiang Sun; Xiaogang Xu; Na He; Zhiqiang Zhang; Huijie Hu; Xingwang Qie; Dayi Zhang; Yuguo Tang; et al. (Analytica Chimica Acta, 2023)

Gelatin Methacrylate (GelMA)-Based Hydrogels for Cell Transplantation: an Effective Strategy for Tissue Engineering - Shining Xiao; Tengfei Zhao; Jingkai Wang; Chenggui Wang; Jiangnan Du; Liwei Ying; Jiangtao Lin; Caihua Zhang; Wanglu Hu; Linlin Wang; Kan Xu (Stem Cell Reviews and Reports, 2019)